Early-life exposure to home dampness associated with health effects among children in Chongqing, China. (December 2015) - Wang, Han; Li, Baizhan; Yu, Wei; Wang, Juan; Norback, Dan
Abstract: Associations between early-life exposure to perinatal dampness problems and health effects among 2917 children (3–6 years) were evaluated in this study. After adjusted for gender, age, family history of asthma or allergies, environmental tobacco smoke exposure, gestation age and house location in the logistic regression models, perinatal exposure to dampness indicators was observed to be strongly associated with some respiratory and allergic symptoms in the last 12 months, including wheezing, cough at night, rhinitis and eczema. The prevalence of theses respiratory and allergic symptoms in the last 12 months was significantly increased with perinatal-only exposure to most dampness indicators and was further increased with continuous exposure (perinatal plus current exposure). There was almost no such significant increase with current-only exposure. This study found less association between perinatal-only exposure and doctor-diagnosed diseases, and these associations may be explained by recall bias. Early-life exposure to perinatal dampness reported by parents was significantly associated with some current respiratory and allergic symptoms among children in Chongqing, China. Hence, it is necessary to pay attention to early living environment, especially home dampness, although the mechanisms are still unclear. Highlights: Perinatal-only exposure to dampness was significantly associated with some current respiratory and allergic symptoms. No such significant increases of current respiratory and allergic symptoms with current-only exposure to dampness. Less association between perinatal exposure to dampness and doctor-diagnosed diseases was found.